Effect of hot corrosion demeanour on aerospace-grade Hastelloy X made by pulsed and constant current arc welding in molten salts at 820 °C. Issue 3 (August 2020) - Sathishkumar, M; Subramani, P; Natesh, M; Venkateshkannan, M; Arivazhagan, N; Manikandan, M
Abstract: The effect of hot corrosion tendency of Hastelloy X weldment made by pulsed current tungsten inert gas (PCTIG) and constant current tungsten inert gas (CCTIG) welding has been studied. The welding has been done using ERNiCrCoMo-1 (Mo-1) filler. The hot corrosion demeanour of the Hastelloy X has studied in two different molten salt circumstance such as MS-1 (molten salt-1) (75Na2 SO4 + 20V2 O5 + 5NaCl) and MS-2 (molten salt-2) (75Na2 SO4 + 25V2 O5 ) for 25 cycles (one hour in each cycle) at 820 °C. The MS-1 substrate shows the maximum weight gain compared to MS-2. Also, the largest parabolic constant (Kp ) is observed for PCTIG MS-1. The existence of NaCl in MS-1 has improved the corrosion rate by generating more spallation and exfoliation on the surface. The trends of hot corrosion resistance are following the order of, CCTIG Mo-1 MS-1 <Base Metal MS-1 <PCTIG Mo-1 MS-1 <Base Metal Mo-1 MS-2 <CCTIG MS-2 < PCTIG Mo-1 MS-2. The smaller grain size and higher protective oxides (NiO, NiFe2 O4, NiCr2 O4, and Cr2 O3 ) developed in PCTIG MS-1 and MS-2 improves the corrosion resistance compared to coarser gains and fewer protective oxides in CCTIG MS-1 and MS-2, respectively. The non-protective oxides (Fe2 O3 and MoO3 ) improved the corrosion rate of the substrate. From this investigation, it is clear that PCTIG weldment in the MS-2 environment is providing better protection to corrosion at 820 °C.